Tatort Politbüro - Przybylski, Peter (Rowohlt, 1991)
Peter Przybylski: Tatort Politbüro. Die Akte Honecker. Verlag Rowohlt Berlin, Berlin 1991. 427 Seiten, 29,80 DM
Includes bibliographical references (p. 416-[422]) and index
Keywords: Biografie; Honecker; Erich; Heads of state